The Influence of Return on Assets and Debt to Equity Ratio on Company Value - Dinna Charisma; Ari Bramasto; Olivia Ardan Ameswari (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2021)
The value of the company is oriented towards the future of the company, so it is expected that every decision making must consider the value of the company. This study formulates several problems, namely the analysis of the values of return on assets and the ratio of debt to equity partially in increasing the Company Value of 11 business entities whose capital is all or partly owned by the government that has been listed on the Indonesia Stock Exchange for the Year 2017-2019. The author's purpose in conducting this research is to find out the values of return on assets and the ratio of debt to Equity to the company value. The quantitative approach used in this research is descriptive and verificative data analysis using classical assumptions including normality, autocorrelation, multicollinearity, heteroscedasticity, and hypothesis testing with multiple linear regression analysis. The results of this study found that Return on Assets has a significant effect on Company Value. The results of this study can be used as input and information about the implementation of Return on Assets and Debt to Equity Ratio which can be used as a basis for knowing the value of BUMN companies that have registered on the Indonesia Stock Exchange.